2013
DOI: 10.1074/mcp.m113.029579
|View full text |Cite
|
Sign up to set email alerts
|

Sucrose-induced Receptor Kinase SIRK1 Regulates a Plasma Membrane Aquaporin in Arabidopsis

Abstract: The transmembrane receptor kinase family is the largest protein kinase family in Arabidopsis, and it contains the highest fraction of proteins with yet uncharacterized functions. Here, we present functions of SIRK1, a receptor kinase that was previously identified with rapid transient phosphorylation after sucrose resupply to sucrosestarved seedlings. SIRK1 was found to be an active kinase with increasing activity in the presence of an external sucrose supply. In sirk1 T-DNA insertional mutants, the sucrose-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
108
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(119 citation statements)
references
References 104 publications
9
108
1
1
Order By: Relevance
“…Furthermore, there are seven phosphoproteins identified by more than two unique phosphopeptides; because a single phosphopeptide could uniquely identify a specific protein, there are 158 phosphoproteins identified by a single phosphopeptide. Phosphorylation occurred on 86% Ser, 16% Thr, and 0.2% Tyr (two sites) residues (Supplemental Table S1), which is comparable with previous studies Engelsberger and Schulze, 2012;Wu et al, 2013;Supplemental Table S3). …”
Section: Early Changes In Protein Phosphorylation In Response To Stresssupporting
confidence: 79%
“…Furthermore, there are seven phosphoproteins identified by more than two unique phosphopeptides; because a single phosphopeptide could uniquely identify a specific protein, there are 158 phosphoproteins identified by a single phosphopeptide. Phosphorylation occurred on 86% Ser, 16% Thr, and 0.2% Tyr (two sites) residues (Supplemental Table S1), which is comparable with previous studies Engelsberger and Schulze, 2012;Wu et al, 2013;Supplemental Table S3). …”
Section: Early Changes In Protein Phosphorylation In Response To Stresssupporting
confidence: 79%
“…A sugar-induced receptor kinase was recently shown to phosphorylate the C terminus of several PIP2s (Wu et al, 2013). Here, we identified OST1 as a novel, potent regulator of PIPs through action at a distinct phosphorylation site.…”
Section: Aquaporin Phosphorylation and Aba-dependent Signalingmentioning
confidence: 88%
“…Phosphorylation of eIF4B and PAPB is important for their interaction, which, in turn, enhances the ATPase and RNA helicase activity of eIF4A (Bi and Goss, 2000). Plant eIF4A is phosphorylated in response to heat stress and hypoxia (Webster et al, 1991;Le et al, 1998), and proteomic analysis of phosphorylation states under a variety of conditions suggests at least three phosphopeptides for eIF4A1 and four for eIF4A2 (Boex-Fontvieille et al, 2013;Umezawa et al, 2013;Wang et al, 2013;Wu et al, 2013;Zhang et al, 2013), as indicated by the PhosPhAt database (Heazlewood et al, 2008;Durek et al, 2010;Zulawski et al, 2013).…”
mentioning
confidence: 99%